Effects of low and high frequency actuation on aerodynamic performance of a supercritical airfoil - Abdolahipour, Soheila (Frontiers in Mechanical Engineering, 2023)
The main objective of this study is to investigate the effects of low and high frequency actuation in improving the aerodynamic performance of the supercritical airfoil with the approach of using it in a high-lift or flight control device. For this purpose, a flow control numerical simulation is performed on a supercritical airfoil with NASA SC(2)-0714 cross section using a pulsed jet at the chord-based Reynolds number of 1 × 106. The pulsed jet actuation with different reduced frequencies of 0.2, 1, 1.2, 2.4, 4, 6, and 12 is implemented on the upper side of the airfoil surface upstream of the separation point of the uncontrolled case. The aerodynamic efficiency improvements are investigated by extracting the results of time-averaged and instantaneous aerodynamic forces for all cases. The study compares the flow streamline, Q-criterion contour, and surface pressure distribution to examine how the separated flow configuration over the airfoil responds to different actuation frequencies. The results indicate that pulsed jet actuation effectively postpones the flow separation. A comparison of the time-averaged aerodynamic coefficients at different actuation frequencies revealed that utilizing a low actuation frequency range maximizes lift, while a high frequency range minimizes drag. In addition, the aerodynamic efficiency of the supercritical airfoil improves across all controlled scenarios, with the optimal increase in aerodynamic efficiency of 28.62% achieved at an actuation frequency of F+ = 1.